Landscape simplification weakens the association between terrestrial producer and consumer diversity in Europe. (15th February 2017) - Dainese, Matteo; Isaac, Nick J. B.; Powney, Gary D.; Bommarco, Riccardo; Öckinger, Erik; Kuussaari, Mikko; Pöyry, Juha; Benton, Tim G.; Gabriel, Doreen; Hodgson, Jenny A.; Kunin, William E.; Lindborg, Regina; et al.
Abstract: Land‐use change is one of the primary drivers of species loss, yet little is known about its effect on other components of biodiversity that may be at risk. Here, we ask whether, and to what extent, landscape simplification, measured as the percentage of arable land in the landscape, disrupts the functional and phylogenetic association between primary producers and consumers. Across seven European regions, we inferred the potential associations (functional and phylogenetic) between host plants and butterflies in 561 seminatural grasslands. Local plant diversity showed a strong bottom‐up effect on butterfly diversity in the most complex landscapes, but this effect disappeared in simple landscapes. The functional associations between plant and butterflies are, therefore, the results of processes that act not only locally but are also dependent on the surrounding landscape context. Similarly, landscape simplification reduced the phylogenetic congruence among host plants and butterflies indicating that closely related butterflies become more generalist in the resources used. These processes occurred without any detectable change in species richness of plants or butterflies along the gradient of arable land. The structural properties of ecosystems are experiencing substantial erosion, with potentially pervasive effects on ecosystem functions and future evolutionary trajectories. Loss of interacting species might trigger cascading extinction events and reduce the stability of trophic interactions, as well as influence the longer term resilience of ecosystem functions. This underscores a growing realization that species richness is a crude and insensitive metric and that both functional and phylogenetic associations, measured across multiple trophic levels, are likely to provide additional and deeper insights into the resilience of ecosystems and the functions they provide. Abstract : Land‐use change is one of the main anthropogenic drivers of species loss, yet its consequence on other components of biodiversity is poorly understood. By investigating the trophic associations between primary producers and consumers along a gradient of landscape simplification across Europe, we show a loss of both functional and phylogenetic associations between plants and butterflies in landscapes now dominated by arable land. These processes occurred even without immediate reductions of species richness. This approach significantly advances our understanding of the functional consequences of species associations' loss for biodiversity in a changing world. It provides an innovative tool for early warning of alteration in ecosystem functioning.